Autofluorescence-Based Identification and Functional Validation of Antennal Gustatory Sensilla in a Specialist Leaf Beetle - Pentzold, Stefan; Marion-Poll, Frédéric; Grabe, Veit; Burse, Antje (Frontiers in Physiology, 2019)
Herbivorous insects mainly rely on their sense of taste to decode the chemical composition of potential hosts in close range. Beetles for example contact and scan leaves with their tarsi, mouthparts and antennal tips, i.e. appendages equipped with gustatory sensilla, among other sensillum types. Gustatory neurons residing in such uniporous sensilla detect mainly nonvolatile compounds that contribute to the behavioural distinction between edible and toxic plants. However, the identification of gustatory sensilla is challenging, because an appendage often possesses many sensilla of distinct morphological and physiological types. Using the specialised poplar leaf beetle (Chrysomela populi, Chrysomelidae), here we show that cuticular autofluorescence scanning combined with electron microscopy facilitates the identification of antennal gustatory sensilla and their differentiation into two subtypes. The gustatory function of sensilla chaetica was confirmed by single sensillum tip-recordings using sucrose, salicin and salt. Sucrose and salicin were found at higher concentrations in methanolic leaf extracts of poplar (Populus nigra) as host plant compared to willow (Salix viminalis) as control, and were found to stimulate feeding in feeding choice assays. These compounds may thus contribute to the observed preference for poplar over willow leaves. Moreover, these gustatory cues benefited the beetle’s performance since weight gain was significantly higher when C. populi were reared on leaves of poplar compared to willow. Overall, our approach facilitates the identification of insect gustatory sensilla by taking advantage of their distinct fluorescent properties. This study also shows that a specialist beetle selects the plant species that provides optimal development, which is partly by sensing some of its characteristic nonvolatile metabolites via antennal gustatory sensilla.